The Influence of Social Media Marketing And Product Quality On Purchase Intention of Pesticides With Brand Awareness As A Mediating Variable (Study On Farmer Groups In Indramayu Regency) - Arie Eka Prasetia Rizki; Aam Bastaman; Zainul Kisman (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2026)
The objective of this study is to analyse the influence of social media marketing and product quality on pesticide purchase intention, with brand awareness as a mediating variable. This study was conducted among farmer groups in Indramayu Regency, considering the importance of digital marketing and product quality in influencing farmer purchasing behaviour. The research approach used was quantitative with primary data. The sampling technique used incidental sampling. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results showed that social media marketing had no influence on brand awareness, product quality influence brand awareness, social media marketing influence purchase intention, product quality influence purchase intention, brand awareness influence purchase intention, brand awareness did not mediate the influence of social media marketing on purchase intention, and brand awareness significantly mediated the influence of product quality on purchase intention. These results imply that improving product quality is a key factor in building brand awareness and purchase intention among farmers, while social media marketing is more effective in directly driving purchase intention. This research is expected to contribute academically to the development of marketing management studies and provide practical considerations for pesticide companies in designing more effective marketing strategies.